Post-COVID syndrome in urology - Ekaterina V. Kulchavenya (LLC "MEDIAFORMAT", 2022)
The review of more than 50 domestic and foreign literary sources, concerning the sequelae of novel coronavirus infection that affect human genitourinary system and fertility potential, has been performed, which also demonstrates some treatment possibilities for the emerging complications. The review has made it possible to reach the following conclusion: COVID-19 is a multisystem disease that affects multiple organs; pathogen eradication does not mean full recovery, acute or chronic post-COVID syndrome usually develops. It is advisable to repeat the course of Selzinc Plus for prevention and treatment of novel coronavirus infection; Selzinc Plus should be used to protect or restore male fertility potential after novel coronavirus infection. COVID-19 can exacerbate the existing OAB or trigger the development of OAB. Trospium chloride (Spasmex) is the best drug for treatment of OAB in cases of exposure to polypharmacy or in elderly patients.